Manajemen risiko pada sistem penyediaan air minum (SPAM) perpipaan dengan metode failure mode and effect analysis dan fault tree analysis di Kabupaten Minahasa Utara - Stania Ekarista Bitty; Liany Amelia Hendratta; Arthur Haris Thambas; Grace Malingkas (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
The construction of a piped Drinking Water Supply System in North Minahasa Regency is very much needed to meet the community's access to drinking water needs. Apart from planning and implementing SPAM construction to achieve quality and sustainable drinking water services, a risk management process is also needed to reduce and anticipate system failures. Through this research, failures and risks in the SPAM development process in North Minahasa Regency can be analyzed using appropriate risk management methods. This is to ensure the sustainability and reliability of SPAM for the communities served. To obtain the data needed in this research, researchers conducted brainstorming, direct observations in the field, interviews with parties involved in SPAM development, and filled out questionnaires. The data obtained is then analyzed using the risk management process, starting from the stages of risk identification, risk assessment, risk management, and implementation of risk management. From the results of the risk assessment using the Failure Mode and Effect Analysis (FMEA) method and the Fault Tree Analysis (FTA) method, 85 risks were identified. In the technical planning for SPAM implementation there are 19 risks, raw water units 28 risks, production units 19 risks, distribution units 12 risks, and service units 7 risks. Each SPAM component is taken for potential risk by calculating the highest RPN value, namely 324.76, for the risk of workers not using K3 equipment. Using the fault tree in the FTA method, we get 13 basic events for the risk of delays in work implementation, 11 basic events for the risk of workers not using K3 equipment, 12 basic events for construction implementation that does not follow implementation methods and plan drawings, 12 basic events for the risk of pipe leaks, and 12 basic events for water use that are not recorded by the water meter. The risk management process for piping SPAM in this research can be a reference framework for implementing further SPAM development.